Astrocytes and microglia in neurodegenerative diseases: Lessons from human in vitro models. (May 2021) - Franklin, Hannah; Clarke, Benjamin E.; Patani, Rickie
Highlights: Astrocytes and microglia key fulfil homeostatic and immune functions in the CNS. Dysfunction of these cell types is implicated in neurodegenerative diseases. Understanding cellular autonomy and early pathogenic changes is a key goal. New human iPSC models will inform on disease mechanisms and therapy development. Abstract: Both astrocytes and microglia fulfil homeostatic and immune functions in the healthy CNS. Dysfunction of these cell types have been implicated in the pathomechanisms of several neurodegenerative diseases. Understanding the cellular autonomy and early pathological changes in these cell types may inform drug screening and therapy development. While animal models and post-mortem tissue have been invaluable in understanding disease processes, the advent of human in vitro models provides a unique insight into disease biology as a manipulable model system obtained directly from patients. Here, we discuss the different human in vitro models of astrocytes and microglia and outline the phenotypes that have been recapitulated in these systems.